2021
DOI: 10.1111/mcn.13198
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with adverse nutritional status of children in sub‐Saharan Africa: Evidence from the Demographic and Health Surveys from 31 countries

Abstract: Undernutrition is linked to almost half of all deaths in under-five children. In 2019, 144 million under-five children suffered from stunting and 47 million suffered from wasting. This study examined the factors that influence adverse nutritional status of children in sub-Saharan Africa. The study used data from the Demographic and Health Surveys (DHS) of 31 countries, which involved 189,195 children under age 5. Binary logistic regression was used to examine the relationships between the independent variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 26 publications
8
19
0
1
Order By: Relevance
“…Malnutrition has various causes, which include illnesses, inadequate diets, and environmental and socioeconomic characteristics [20]. The age of the child in a month [20][21][22][23], gender of the child [24,25], birth size of the child [26,27], birth order [4,28], maternal education [28,29], mother's body mass index [24,29], household wealth index [4,21,30], source of drinking water [22,30], family size [24], region [22], residence [24], religion [31], ethnicity [32], sex of household head [30], husband education level [4,30], breastfeeding status [32,33], sex of children [34,35], diarrhea [32,36], fever and cough [31,32] in the last 2 weeks prior to the survey, birth type of children [22,28], number of under-five children [27], maternal anemia [9] and child anemia [22] were the determinants of children's nutritional status in Gambia which have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malnutrition has various causes, which include illnesses, inadequate diets, and environmental and socioeconomic characteristics [20]. The age of the child in a month [20][21][22][23], gender of the child [24,25], birth size of the child [26,27], birth order [4,28], maternal education [28,29], mother's body mass index [24,29], household wealth index [4,21,30], source of drinking water [22,30], family size [24], region [22], residence [24], religion [31], ethnicity [32], sex of household head [30], husband education level [4,30], breastfeeding status [32,33], sex of children [34,35], diarrhea [32,36], fever and cough [31,32] in the last 2 weeks prior to the survey, birth type of children [22,28], number of under-five children [27], maternal anemia [9] and child anemia [22] were the determinants of children's nutritional status in Gambia which have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the researchers' knowledge, no study has been conducted on the determinants of the coexistence of undernutrition indicators in Gambia. In Nepal, Ethiopia, Uganda, Bangladesh, East Africa, Cameron, Ghana, Sub-Sahara Africa, Gambia, Tanzania, and Mozambique [4,10,20,22,27,28,[33][34][35][37][38][39], stunting, underweight, and wasting have all been extensively studied. However, little attention has been paid to their association, and literature is scarce, particularly in Gambia, so we will conduct a separate analysis of stunting, underweight, and wasting in children under the age of five, as previously done by studies [4,10,20,22,27,28,[33][34][35][37][38][39], using ordinal or binary logistic regression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of mass media has also been associated with reduced rates of stunting. In sub-Saharan Africa, stunting is significantly associated with mass media exposure [ 27 - 29 ]. Studies conducted in other low- or middle-income countries, such as Bangladesh [ 30 ], Indonesia [ 31 ], and India [ 32 ] also found that the exposure of mother to the mass media is associated with stunting.…”
Section: Introductionmentioning
confidence: 99%
“…The gender of infants and young children and their age are characterized as variables that influence wasting [ 17 , 22 , 23 ]. Wasting is also linked to educational status [ 24 , 25 ], occupational status [ 26 ], family food insufficiency [ 27 , 28 ], and dietary intake [ 21 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%